Adapter sleeves are essential for ceramic heads in hip revision surgery. (January 2020) - Falkenberg, Adrian; Dickinson, Emilie C.; Morlock, Michael M.
Abstract: Background: Removing a head during isolated acetabular revision surgery can cause damage to the stem taper surface from extraction tool contact. Implanting a ceramic head on the damaged stem taper might elevate the fracture risk, which can be mitigated with the use of titanium adapter sleeves. The aim of this study was to investigate whether the improved fracture strength of modern generation ceramic heads allows the direct implantation on damaged stem tapers without an adapter sleeve. Methods: Finite element models of taper junctions with and without adapter sleeve were generated. Different stem taper damages were modelled to investigate the influence on the ceramic head fracture load under axial compression. Findings: Heads without adapter sleeves exhibited slightly higher or equal fracture strengths compared with sleeved heads for most scenarios. However, a small metal elevation on the stem taper caused a drastic decrease of the fracture strength if no adapter sleeve was used (−96%). The sleeved head was not influenced by the metal elevation damage. Interpretation: Adapter sleeves are essential to ensure patient safety and prosthesis longevity whenever implanting ceramic heads on used stem tapers. Highlights: Head removal during revision surgery can cause stem taper damage. Stem taper damages showed drastic reductions to ceramic head fracture strength. Adapter sleeves have the potential to compensate stem taper damages.